Pengaruh Pemberian GA3 dan Ekstrak Paku Sayur (Diplazium esculentum) terhadap Kualitas Hasil Buah Anggur (Vitis vinifera L.) Varietas Kediri Kuning - Purba, Reza Stefany; Astawa, I Nyoman Gede; Dwiyani, Rindang (Agrotrop : Journal on Agriculture Science, 2024)
Effect of GA3 and Vegetable Spike Extract (Diplazium esculentum) on the Yield Quality of Grape (Vitis vinifera L.) Kediri Kuning Variety. This study aims to determine the effect of vegetable fern extract solution on the quality of grapes of Kediri Kuning variety and the concentration that can improve the quality of grapes. This research uses RAK (Randomized Group Design) with the treatment of vegetable fern extract consisting of 5 levels with 5 replicates, namely P0 = Control, PG = GA3 500 ppm, PS25 = 25%, PS50 = 50%, PS75 = 75%. The results showed that the treatment of vegetable fern extract solution gave an influence on the variables of titratable acid content, fruit bunch length, number of seeds per fruit, vitamin c content, antioxidant properties content, and seed weight per fruit, tannin content. Dipping the vegetable fern extract solution in the stadia before flower blossom can improve the quality of Kediri Kuning grapes, seen in titratable acid content, fruit bunch length, number of seeds per fruit, weight of seeds per fruit, vitamin C content, antioxidant properties, and tannin content. The concentration of 50% vegetable spike extract is able to provide the best results and quality to improve the quality of Kediri Kuning grapes.